Perancangan Desain Pedoman Manajemen Krisis Berbasis Teknologi Artificial Sebagai Inovasi di Bidang Kehumasan - Wina Puspita Sari; Muria Putriana; Indah Fajar Rosalina; Qoryna Noer Seyma El Farabi; Kayla Sulendra Kusumah; Muhammad Ardi Himawan; Muhammad Faishal Alghoniyyu; Najwa Aulia Khansa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the extent to which artificial intelligence (AI) technologies are utilized by government institutions and companies in public relations (PR) practices, and to relate these findings to crisis management strategies. Using a descriptive quantitative approach, data were collected through surveys and interviews involving 23 institutions, consisting of 19 government agencies and 4 private companies. The results show that ChatGPT is the most widely used AI tool (56%), followed by Gemini (34%) and QuillBot (14%). Most other tools showed low usage rates, with a high percentage falling under the “unknown” category, indicating limited information and awareness regarding AI technologies within PR environments. These findings have strategic implications in the context of crisis management, as the speed and accuracy of information dissemination are highly dependent on technological adaptability. The integration of AI tools into public communication systems can serve as both a preventive and responsive solution to reputational and operational crises. Therefore, policies are needed to enhance digital literacy and provide technical training on AI utilization for PR practitioners in both the public and private sectors.